2007
DOI: 10.1007/s10535-007-0149-y
|View full text |Cite
|
Sign up to set email alerts
|

In vitro selection of salt tolerant cell lines in Solanum tuberosum L.

Abstract: Cell lines able to grow on media containing 50, 100, 150 or 200 mM NaCl were established from potato callus cultures by direct recurrent selection or gradual selection. In callus subjected to direct selection only small clusters of cells survived on medium with 150 or 200 mM NaCl, whereas on 100 mM small cell portions appear necrotic. When cell lines were obtained by successive subcultures on media with increased concentrations of NaCl, salt-tolerant calli were more compact and developed a greenish colour free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
44
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 44 publications
10
44
0
Order By: Relevance
“…However 200 mM NaCl tolerant calli obtained either by direct or indirect selection process did not sustained a regular growth on salt supplemented media, these calli suffered with time a decrease in growth and all callus tissues died when the culture period was prolonged beyond one month. A similar response was reported in salt tolerant potato calli lines (Queiros, et al, 2007) and in Chrysanthemum sp. (Hossain, et al, 2007).…”
Section: Growth Of Callussupporting
confidence: 85%
See 2 more Smart Citations
“…However 200 mM NaCl tolerant calli obtained either by direct or indirect selection process did not sustained a regular growth on salt supplemented media, these calli suffered with time a decrease in growth and all callus tissues died when the culture period was prolonged beyond one month. A similar response was reported in salt tolerant potato calli lines (Queiros, et al, 2007) and in Chrysanthemum sp. (Hossain, et al, 2007).…”
Section: Growth Of Callussupporting
confidence: 85%
“…And in several other plant species such as, canola (Tyagi & Rangaswamy, 1997, Jain, et al, 1991a finger millet, (Pius, et al 1993) Cotton (Gosset,t et al, 1994 Potato (Olmos & Hellin, 1996;Queiros, et al, 2007) rice (Dang & Nuguyen, 2003;Shankdhar et al, 2000) Sunflower (Davenport, et al, 2003) chilli (Venkataiah, et al, 2004) sugarcane (Gandonou, et al, 2006).…”
Section: Establishment Of Salt Tolerant Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…The MV treatments were carried out by soaking plant leaf discs (12 mm in diameter) in 2 ml of distilled water or in 1 or 3 μM MV for 12 or 24 hours at 25°C under continuous light. For the drought and salt stress treatments, shoot parts (2 cm) from cultured WT and transgenic potato plants were excised and transferred to MS medium supplied with 5% (w/v) polyethylene glycol (PEG 6000) for drought stress (Gopal and Iwama 2007) or 50 mM NaCl for salt stress (Queirós et al 2007). ) and maintained for 3 weeks under controlled conditions (25°C, 16 h light, 8 h dark photoperiod).…”
Section: Methylviologen Drought and Salt Stress Treatmentsmentioning
confidence: 99%
“…Therefore, the level of malonyldialdehyde, produced during peroxidation of membrane lipids, is often used as an indicator of oxidative damage [31]. It has been reported that selected callus lines of Solanum tuberosum subjected to NaCl showed an increase in lipid peroxidation in comparison with salt tolerant lines [32].…”
Section: Characterization Of Salt-or Drought-tolerant Plants During Imentioning
confidence: 99%